2012
DOI: 10.4049/jimmunol.1201371
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Ionizing Radiation Induces the Migration of Cutaneous Dendritic Cells by a CCR7-Dependent Mechanism

Abstract: In the event of a deliberate or accidental radiological emergency, the skin would likely receive substantial ionizing radiation (IR) poisoning which could negatively impact cellular proliferation, communication, and immune-regulation within the cutaneous microenvironment. Indeed, as we have previously shown, local IR exposure to the murine ear causes a reduction of two types of cutaneous dendritic cells (cDC), including interstitial DC (iDC) of the dermis and Langerhans cells (LC) of the epidermis, in a dose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 44 publications
4
32
1
Order By: Relevance
“…Further myeloablative conditioning by total body irradiation (TBI) before transplantation and anti-thymocyte globulin (ATG) prophylaxis against aGvHD may interact with and modulate the effect of subsequent photochemotherapy. Ionizing irradiation is known to damage DNA and to alter the dendritic cell populations of the skin - effects shared with photochemotherapy [11,12,13]. ATG is generally decreasing both the host dendritic cell population, which is a target for donor cell-mediated immunity, and the donor dendritic cell population, which is a director of donor T-cell tropism [14].…”
Section: Introductionmentioning
confidence: 99%
“…Further myeloablative conditioning by total body irradiation (TBI) before transplantation and anti-thymocyte globulin (ATG) prophylaxis against aGvHD may interact with and modulate the effect of subsequent photochemotherapy. Ionizing irradiation is known to damage DNA and to alter the dendritic cell populations of the skin - effects shared with photochemotherapy [11,12,13]. ATG is generally decreasing both the host dendritic cell population, which is a target for donor cell-mediated immunity, and the donor dendritic cell population, which is a director of donor T-cell tropism [14].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of CCL21 impairs cellular retention leading to an attenuated immune response. Indeed, upregulation of CCL21 prior to hapten challenge promotes CCR7 + cells egress from the skin leading to impaired CHS responses (67). Our data indicated that down-regulation of CCL21 could be reversed by HPSE blockade or PI3K activation, which were down-stream of VEGFR-3 signaling.…”
Section: Discussionmentioning
confidence: 55%
“…It was reported that local irradiation triggered migration of LC in epidermal in a time and dose dependent manner [6]. Recently Cummings et al [2] found that sub-lethal irradiation induced cutaneous DC migration to the draining LN. In this study our data showed that WBI caused a depletion of cDC in epidermal and dermal.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ryan et al found that sub-lethal irradiation induced cDC migration from skin to the draining LN [2], while our department had found that ionizing radiation inhibited the migration capacity of DC in vitro [7]. Furthermore, as occupational exposure is becoming a major part of the radiation exposure, the migration capacity of cDC after moderate dose of whole body irradiation (WBI) is drawing more and more attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation